Modelagem da vulnerabilidade e perigo de contaminação da água subterrânea pela atividade agrícola no alto trecho da Bacia do Paraguaçu, Estado da Bahia - Oliveira, Ana Isabel Leite (2011)
The intense pressure that natural resources are suffering as a result of population increase and economic growth drives the development of research to provide the management tools suitable for land management and protection of environmental systems. In the basin Paraguaçu, in his high stretch, boasting spring waters of the third largest hydrographic basin in the state of Bahia, the exploitation of natural resources is intense, especially agribusiness. This context led to the assessment of the vulnerability and danger of groundwater contamination, focusing on agriculture, defining this geographical area as the unit of analysis. The modeling procedure widely used geographic information technologies, based on the principles of the methods GOD and POSH, with the application of cumulative maps algebra operations. As result, we generated three main models: (1) Vulnerability to Contamination of aquifers, (2) Potential for Underground Contaminant Load Insert by Agricultural Activity, and (3) Priority Areas for Quality Control of Groundwater. The region is characterized by a predominance of sandy cover with low content of clay overlying unconfined aquifers whose water table remains above 20 meters, which means great exposure of the groundwater. Modeling results showed that 96% of the area has high vulnerability and 16% high potential of introducing contaminant load. With this combination, high vulnerability and high danger, priority areas to control contamination were indicated, in order to avoid future risks to the ecosystem and human health.